PEMBERDAYAAN METODE QIROATI DALAM MENINGKATKAN KEMAMPUAN AL-QUR’AN LANSIA TPA FATIMAH TAHUN 2023 - Abidin, Zaenal; Isnaini, Isnaini (Jurnal Indonesia Mengabdi, 2023)
The aim of this service is that it is hoped that the public will know the Qiroati Method in improving the ability to read the Al-Qur'an for the elderly and disabled at the Fatimah Al-Qur'an Education Park, Semarang. Apart from that, it is hoped that we can find out the efforts and results made by ustadzah and students in overcoming obstacles to empowering the Qiroati Method in Learning to Read the Al-Qur'an at the Fatimah Al-Qur'an Education Park, Semarang. This service was carried out at the Fatimah Al-Qur'an Education Park, Semarang. Coaching participants in this service. consisting of: caregivers, teaching ustadzah, and students at the Al-Qur'an Fatima Semarang Education Park. This service uses lecture and question and answer methods in discussion forums at the Fatimah Al-Qur'an Education Park, Semarang. The Qiroati learning method is a method that is suitable for learning in the post-pandemic era. The obstacle factor that occurred during the training was that there were several students who were not familiar with this method